Is root bark different from stem bark in the Cerrado plant community? - Vergilio, Paula Cristina Benetton [UNESP]; Marcati, Carmen Regina [UNESP]; Rosell, Julieta Alejandra (De Gruyter, 2025)
Summary Bark, the group of tissues found outside the cambium, is a complex system comprising mainly the secondary phloem and the periderm, with functions ranging from photosynthate transport to plant protection. Although the structure of bark has been widely examined, little is known about the variation of its structure and function under different ecological conditions, such as the contrasting environments experienced by underground roots and aboveground stems. Here, we compared the qualitative and quantitative bark anatomy of roots and stems, and examined the stem periderm ontogeny, in 15 woody plant species from the Cerrado, a fire-prone ecosystem, aiming to identify the main bark trends in the plant community. Our results showed that the qualitative traits of the secondary phloem were similar between roots and stems, confirming the known diagnostic value of this tissue. Likewise, the quantitative traits of sieve tubes, sclerenchyma, and axial parenchyma were also similar between the organs. However, rays were taller in the root, which likely increases radial conduction and storage, and may contribute to plant survival and post-fire resprouting. Fire protection and pathogen resistance were indicated by stem periderm traits, such as a thicker phellem with larger and thicker-walled cells and a more developed rhytidome, although the phelloderm was quite similar between organs. The protective traits of stem periderm were present since the first-formed periderm. In addition, some species retained primary tissues in one or both organs, and showed lenticels mainly in roots, suggesting that the bark’s role in roots and stems is even more complex than previously expected. This study highlights key differences between root and stem bark, particularly in the secondary phloem and the periderm, which are critical for plant survival in fire-prone environments.